Pilot study investigating the impact of serial ingestion or co-ingestion of creatine and sodium bicarbonate on performance following completion of a hypertrophy type resistance exercise workout - Ispoglou, T.; Legget, D.; Driscoll, J.; Kaldaridou, K. (Athens Journal of Sport, 2016)
Purpose: To examine the ergogenic potential of creatine (Cr), sodium bicarbonate (SB),and Cr+SBafter completion of a resistance exercise bout (REB). Methods: Following recruitment, 27 trained males (26.8±5.7 years old) completed a one repetition aximum strength (1RM) test in the parallel squat (120.9±28.2 kg). Participants then followed a standardised meal plan for 4 days whilst ingesting one of 4 supplements, and on day 5 they undertook the REB. This was a double blind randomised placebo-controlled study where participants ingested one of the following: Placebo (PLA, n=7), Cr (20 g/d-1& PLA, n=8), SB (0.5 g/kg-1/d-1 PLA, n=6), andCr+SB (5 g/d-1of Cr & 0.5 g/kg-1/d-1SB, n=6) divided in 4 doses. The REB consisted of 4x10 repetitions (70% of 1RM, 1½ min recovery). The primary performance outcome was a 5th set (70% of 1RM) performed to volitional exhaustion.Blood glucose and lactate, heart rate, ratings of perceived exertion, sickness and stomachache scales, and time to complete each set were also recorded. Results: Participants in Cr, SB, and Cr+SB completed the required number of repetitions at 70% of 1RM however in PLA they completed the same repetitions at lower intensity (68+3.4%). Participants in PLA, Cr, SB, and Cr+SB completed 8(±1.6), 11(±5.5), 9(±3.7), and 11(±3.3) repetitions respectively during the 5th set. Despite the fact that no significant differences were observed in performance, small (SB: 0.4) and moderate effect (Cr: 0.7; Cr+SB: 1.0) sizes were observed in relation to PLA. Body mass increasedsignificantly after Cr (78.1±8.9 kg pre vs 79.1±8.9 kg post, p<0.05). No other significant differences existed in recorded variables. Conclusions: Performance gains were of higher magnitude in the Cr+SB and Cr groups. Co-ingestion of a small amount of Cr (5 g/d-1) with a standard dose ofSB (0.5 g/kg-1/d-1) appears to be equally beneficial asingestion of a standard dose of Cr (20 g/d-1). The Cr+SB was not associated with significant gains in body mass which may be beneficial in sports where size gainsmay negate performance. Further research is required, with larger sample size, and specific athletic populations in order to confirm the findings of the current study